Caracterización de la chuquiragua (Chuquiraga jussieui) con perspectivas agroindustriales - Palma Bastidas, Milton Alexander (2019)
In the last decades the search for natural products has been growing. This framework includes the chuquiragua (Chuquiraga jussieui), a plant native to the Ecuadorian Andes that has been used traditionally for the treatment of diseases, in this sense, the aim of this investigation was to characterize the biochemical profile of the flower of chuquiragua for possible agro-industrial use. The study was conducted in the towns of Chimborazo, Pichincha and Cotopaxi, which are located between 3300 to 4800 meters above sea level. The research involved the identification of the bioactive compounds found in the flower of chuquiragua from laboratory analysis such as ash, moisture, protein, ether extract, crude fiber, nitrogen-free extract, foreign material and antioxidant activity. Concerning the proximal bromatological principles, it was determined that the values obtained comply with the parameters established by the Herbalist Pharmacopoeia of the United Mexican States. The results of the flowers of Chuquiragua jussieui showed the highest values in the province of Cotopaxi in content of foreign material, ashes, moisture, protein while in the locality of Chimborazo presented the highest values in content of ether extract, fiber were found. Finally the locality of Pichincha presented the highest content of nitrogen-free extract. To complete the investigation, the antioxidant activity of the flower of the province of Pichincha was determined by the ABTS radical method, obtaining a 49, 31 percent inhibition percentage. Regarding to the statistical evaluation, a completely randomized block design (DBCA), with three repetitions, was used in the INFOSTAT program.